The Effects of Prebiotic Mannan Oligosaccharide (MOS) Supplementation on Hematology Profile of Native Chickens (Gallus gallus domesticus) - Dewi, Fullan Ausati Putri; Utami, Prima Sukma Rizky; Rusyda, Tsamara Aulia; Kusuma, Dhio Salhisya Marta; Maharani, Disty Putri; Bima, Dewangga Arya; Rachmawati, Kadek (Universitas Airlangga, 2025)
Native chickens (Gallus gallus domesticus) are an important source of animal protein due to their adaptability and relatively simple management. However, their productivity remains limited, which poses a significant challenge in poultry farming. One promising strategy to improve the health and productivity of native chickens is supplementation with Mannan Oligosaccharides (MOS), a prebiotic known to enhance gut microflora balance, strengthen immune responses, and support overall health. This study aimed to evaluate the impact of MOS supplementation on the hematological profile of native chickens. A true experimental method with a control group pre-test post-test design was employed. The results demonstrated that MOS supplementation significantly improved the hematological profile of native chickens. Notable increases were observed in the red blood cell (RBC) count to 2.54 × 10⁶ cells/mm³, white blood cell (WBC) count to 20.30 × 10³ cells/mm³, hemoglobin concentration to 11.4 g/dL, and hematocrit value to 31%. These findings highlight the potential of MOS supplementation to enhance the health and productivity of Native chickens through improvements in key hematological parameters.